Persistence of Gut Microbiota Dysbiosis and Chronic Systemic Inflammation After Cerebral Infarction in Cynomolgus Monkeys - Chen, Yonghong; Liang, Jiahui; Ouyang, Fubing; Chen, Xinran; Lu, Tao; Jiang, Zimu; Li, Jianle; Li, Yuefeng; Zeng, Jinsheng (Frontiers in Neurology, 2019)
Background: The bidirectional interaction between the gut and brain through immune-mediated pathway has been studied. However, the long-term effects of gut microbiota and systemic immune homeostasis after cerebral ischemia still remain unclear. We examined long-term changes in the gut microbiota and systemic inflammatory cytokines after cerebral infarction in cynomolgus monkeys. Methods: Twelve monkeys underwent successful distal M1 segment of the left middle cerebral artery occlusion (MCAO) and were randomly and equally assigned to the MCAO-1.5 m, MCAO-6 m and MCAO-12 m groups, which were sacrificed 1.5 months, 6 months and 12 months after cerebral infarction induction, respectively. Four monkeys that underwent a sham operation were sacrificed 12 months later. The gut microbiota and short-chain fatty acids (SCFAs) were analyzed by 16S rDNA sequencing and gas chromatography mass spectrometry, respectively. Histological examinations of the transverse colon were performed. Plasma D-lactate, zonulin, lipopolysaccharide (LPS), TNF-α, IFN-γ and IL-6 were detected by immunoassay kits. Results: The levels of the Bacteroidetes phylum and Prevotella genus were significantly increased, while the Firmicutes phylum as well as the Faecalibacterium, Oscillospira and Lactobacillus genera were decreased after cerebral infarction. Gut-originating SCFAs were significantly decreased 6 and 12 months after cerebral infarction (P<0.05). Intestinal mucosal damage was evaluated by Chiu’s score. Plasma D-lactate, zonulin, LPS, TNF-α, IFN-γ and IL-6 were significantly increased after cerebral infarction (P<0.05). Additionally, the increases in plasma LPS, TNF-α, IFN-γ and IL-6 after cerebral infarction coincided with overgrowth of the Bacteroidetes phylum (P<0.001). Conclusion: Cerebral infarction induces persistent host gut microbiota dysbiosis, intestinal mucosal damage and chronic systemic inflammation in cynomolgus monkeys.